Changes in haemocoagulation in healthy volunteers after a 1-hour thrombotripsy using a diagnostic 2-4 MHz transcranial probe - Skoloudík, David; Fadrná, Tána; Bar, Michal; Zapletalová, Olga; Zapletal, Ondrej; Blatný, Jan; Penka, Miroslav; Langová, Katerina; Hlustík, Petr; Herzig, Roman; Kanovský, Petr (Journal of thrombosis and thrombolysis, 2008)
INTRODUCTION: The aim was to monitor the changes in haemocoagulation parameters in healthy volunteers after a thrombotripsy with 1-hour transcranial Doppler monitoring using a 2-4 MHz probe. MATERIALS AND METHODS: About 10 healthy volunteers underwent a 1-hour thrombotripsy of the middle cerebral artery (MCA), thrombotripsy of the radial artery and a standard 20-min neurosonologic examination (NSE) in 2-week intervals. Platelet count, aPTT, prothrombin time, fibrinogen, D-dimers, tPA, FDP, alpha-2-antiplasmin (AP), plasminogen, PAI-1 antigen, time of euglobulin clot lysis (ECL), homocysteine, and lipoprotein (a) were examined before, at the end and 24 h after a thrombotripsy. All adverse events were monitored. RESULTS: After a thrombotripsy of the MCA, PAI-1 antigen, tPA antigen, fibrinogen and AP activity were significantly decreased by a mean of 32, 23, 7, and 4% respectively (P < 0.05 in all cases). After a thrombotripsy of the RA, there was a significant decrease in tPA antigen alone by an average of 14% (P < 0.05). Standard NSE did not affect any of the measured factors. CONCLUSIONS: Thrombotripsy with 1-hour TCD monitoring using a 2-4 MHz diagnostic probe may affect the fibrinolytic system in humans.
Keywords: arteria cerebri media; Female; ženské pohlaví; arteria radialis; Blood Coagulation; Time Factors; časové faktory; lidé; Pilot Projects; pilotní projekty; ultrasonografie dopplerovská transkraniální; Male; Aged; Radial Artery; Ultrasonography, Doppler, Transcranial; lidé středního věku; Middle Cerebral Artery; senioři; mužské pohlaví; hemokoagulace; Middle Aged; Humans